Effect of sintering temperature on phase constitution and mechanical properties of WC-1.0 wt% carbon nanotube composites. Issue 1 (January 2018) - Cao, Tin; Li, Xiaoqiang; Li, Jingmao; Zhang, Minai; Qiu, Hao
Abstract: Ultrafine grain WC-1.0 wt% carbon nanotube (CNT) composites were prepared using spark plasma sintering and the influence of sintering temperature on the properties of the composites was investigated. The specimen tested in this study achieved an optimum hardness of 22.81±0.81 GPa and fracture toughness of 8.95±0.38 MPa m 1/2 after sintering at 1700 °C. On applying a sintering temperature of 1900 °C, the mechanical properties of the specimens deteriorated. Raman spectroscopic analysis results indicated that the structure of the CNTs changed and the graphite phase occurred at 1900 °C, which was responsible for the deteriorating hardness, elastic modulus, and fracture toughness. This study provides details of the transformation of the CNTs in the tungsten carbide matrix, indicating that the WC-CNT composites should be sintered at moderate temperatures.